Hepatic drug transporters: the journey so far. (1st February 2016) - Riley, R. J.; Foley, S. A.; Barton, P.; Soars, M. G.; Williamson, B.
ABSTRACT: Introduction : The key role of transporter biology in both the manifestation and treatment of disease is now firmly established. Experiences of sub-optimal drug exposure due to drug-transporter interplay have supported incorporation of studies aimed at understanding the interactions between compounds and drug transporters much earlier in drug discovery. While drug transporters can impact the most pivotal pharmacokinetic parameter with respect to human dose and exposure projections, clearance, at a renal or hepatobiliary level, the latter will form the focus of this perspective. Areas covered : A synopsis of guidelines on which transporters to study together with an overview of the currently available toolkit is presented. A perspective on when to conduct studies with various hepatic transporters is also provided together with structural "alerts" which should prompt early investigation. Expert opinion : Great progress has been made in individual laboratories and via consortia to understand the role of drug transporters in disease, drug disposition, drug-drug interactions and toxicity. A systematic analysis of the value posed by the available approaches and an inter-lab comparison now seems warranted. The emerging ability to use physico-chemical properties to guide future screening cascades promises to revolutionise the efficiency of early drug discovery.